Legal Aspect Marriage in Under Age Child - Christian Daniel Hermes; Rosita Nainggolan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine how the occurrence of underage marriage and how the effects of underage marriage. Marriage is an inner and outer bond which binds themselves to become husband and wife. This study discusses the many impacts that occur due to underage marriage even though the Marriage Law has changed. Law of the Republic of Indonesia No. 16 of 2019 concerning Amendments to Law No. 1 of 1974 concerning Marriage, says "marriage is only permitted if a man and a woman have reached the age of 19 (nineteen) years". This age limit is considered to be explained that the body and soul have matured to be able to carry out marriage, and it is hoped that the existence of an age limit higher than 16 (sixteen) years for women to marry will result in a lower birth rate and reduce the risk of maternal and child mortality. and the fulfillment of children's rights so as to optimize children's growth and development including parental assistance and provide children's access to education as high as possible. The occurrence of underage marriages often occurs because children who have committed juvenile delinquency such as having sex outside of marriage to cause pregnancy and due to parental matchmaking. While the effect of underage marriage is the immaturity of the young mother's age from the marriage, it brings risks to the prospective child and because without mature thinking it makes it easy to divorce, where children become psychological victims of parents who divorce.